2018
DOI: 10.1093/eurpub/cky168
|View full text |Cite
|
Sign up to set email alerts
|

The increased trend of non-drinking alcohol among adolescents: what role do internet activities have?

Abstract: Internet activities were in general not associated with non-drinking among adolescents aged 15-16 years in Sweden. Although, a weak positive association between computer gaming and non-drinking was found in 2012, this effect benefited the vast majority of the boys. The larger alcohol use among those with extensive social media use/chatting may indicate that these online platforms are arenas where adolescents are exposed for positive alcohol preferences and alcohol advertising without parental supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 24 publications
(36 reference statements)
1
34
0
1
Order By: Relevance
“…It has been suggested that the rise in time spent on using information and communication technologies is important in this regard, as adolescents have become too busy with their media pursuits at the expense of activities, such as substance use, that typically occur in face-to-face social interactions [7,10]. However, the extant body of research does not support this assumption [19,33], and a possible role of the use of digital media in this regard may be complex [1].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the rise in time spent on using information and communication technologies is important in this regard, as adolescents have become too busy with their media pursuits at the expense of activities, such as substance use, that typically occur in face-to-face social interactions [7,10]. However, the extant body of research does not support this assumption [19,33], and a possible role of the use of digital media in this regard may be complex [1].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one study has explored the role of online activities on declining adolescent alcohol use (Larm, Raninen, Åslund, Svensson, & Nilsson, 2018). This Swedish study's comparisons between individual survey years pointed in diverse directions: no association between time spent on computers and non-drinking; a positive association between increased social media communication and decreased probability of non-drinking;…”
Section: Youth Leisure Time Activities Using Digital Information and mentioning
confidence: 97%
“…Of 7927 unique studies, 79 (1%) met our inclusion criteria (Aboujaoude et al, 2015;Banjanin et al, 2015;Banyai et al, 2017;Barry et al, 2017;Best et al, 2014Best et al, , 2015Booker et al, 2018;Bourgeois et al, 2014;Boyle et al, 2016;Brunborg et al, 2017;Burnette et al, 2017;Colder Carras et al, 2017;Critchlow et al, 2019;Cross et al, 2015;Curtis et al, 2018;de Lenne et al, 2018;de Vries et al, 2016;Erfani and Abedin, 2018;Erreygers et al, 2018;Fahy et al, 2016;Ferguson et al, 2014;Fisher et al, 2016;Foerster and Roosli, 2017;Foody et al, 2017;Fredrick and Demaray, 2018;Beullens, 2017, 2018;Hamm et al, 2015;Hanprathet et al, 2015;Harbard et al, 2016;Hase et al, 2015;Holfeld and Mishna, 2019;Houghton et al, 2018;Jafarpour et al, 2017;John et al, 2018;Kim et al, 2019;Kim, 2017;Koo et al, 2015;Lai et al, 2018;Larm et al, 2017Larm et al, , 2019…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%